Gender Identity, Co-Working Spouses and Relative Income within Households - Natalia Zinovyeva; Maryna Tverdostup (Institute of Labor Economics (IZA), 2018)
Bertrand, Kamenica and Pan (2015) document that in the U.S. there is a sharp discontinuity to the right of 1/2 in the distribution of households according to the share of income earned by the wife, which they attribute to the existence of a gender identity norm postulating that a wife should earn less than her husband. We propose an alternative explanation for the existence of this discontinuity. We argue that any force that pushes some spouses towards equalizing their earnings, such as family businesses and co-working of spouses, creates a similar discontinuity. Using linked employer-employee data from Finland, we document the existence of a discontinuity of the same magnitude as in the U.S. and show that it can be fully explained by the earnings convergence of spouses who start working together. We also provide evidence suggesting that co-working spouses play an important role in explaining the discontinuity observed in the U.S.
Keywords: D10; J16; J21; 330; co-working spouses; gender identity norms; spouses' relative earnings